2004
DOI: 10.1262/jrd.50.215
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Ovarian Steroids Stimulates Prostaglandin F2.ALPHA. Production Through Nuclear Factor-.KAPPA.B Activation via Oxygen Radicals in Human Endometrial Stromal Cells: Potential Relevance to Menstruation

Abstract: Abstract. The present study was undertaken to investigate whether withdrawal of estrogen and progesterone (EP-withdrawal) stimulates prostaglandin F2α (PGF2α) production through oxygen radical (ROS)-induced NF-κB activation in human endometrial stromal cells (ESC). To study the EPwithdrawal, ESC that had been treated with estradiol (E, 10 -8 M) and medroxyprogesterone acetate (MPA, 10 -6 M) for 12 days were then incubated with or without E+MPA for a further 11 days. PGF2α concentrations in the medium and cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 56 publications
5
102
1
3
Order By: Relevance
“…By contrast, it has been also demonstrated that ROS, including superoxide and hydrogen peroxide, play critical roles in the regulation of ovarian functions, such as oocyte maturation, folliculogenesis, ovarian steroidogenesis, and luteolysis. Thus, there is a delicate balance between ROS and antioxidant enzymes in the ovarian tissue (Shiotani et al 1991;Behrman et al 2001;Sugino et al 2004;Agarwal et al 2005;Agarwal et al 2006;Tatone et al 2008). The imbalance of ROS and antioxidants has been suggested as a mechanism of ovarian aging, as shown by decreased levels of glutathione and glutathione S-transferase in ovulated oocytes from aged mouse or downregulation of superoxide dismutase (Cu/ZnSOD and MnSOD) and catalase genes in human granulosa cells (Tarin et al 2004;Tatone et al 2006;Tatone et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it has been also demonstrated that ROS, including superoxide and hydrogen peroxide, play critical roles in the regulation of ovarian functions, such as oocyte maturation, folliculogenesis, ovarian steroidogenesis, and luteolysis. Thus, there is a delicate balance between ROS and antioxidant enzymes in the ovarian tissue (Shiotani et al 1991;Behrman et al 2001;Sugino et al 2004;Agarwal et al 2005;Agarwal et al 2006;Tatone et al 2008). The imbalance of ROS and antioxidants has been suggested as a mechanism of ovarian aging, as shown by decreased levels of glutathione and glutathione S-transferase in ovulated oocytes from aged mouse or downregulation of superoxide dismutase (Cu/ZnSOD and MnSOD) and catalase genes in human granulosa cells (Tarin et al 2004;Tatone et al 2006;Tatone et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms leading to luteolysis are species specific and complex; nevertheless, PGs play an important role in its regulation. The addition of PGE to cultured ovine (Weems et al 1997), bovine (Kotwica et al 2006), human (Endo et al 1988), and rat luteal cells (Hurwitz et al 2002) increases the production of P. In contrast, the release of PGF 2a initiates luteal regression in domestic livestock (Knickerbocker et al 1988), pigs (Gadsby et al 1990), bovines (Hanselbetween PGs and the response of the antioxidant defenses in different systems is controversial (Sugino et al 2004, Al-Gubory et al 2005, Garrel et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The scarce in-vivo reports studying the CL of rats and sheep have shown the importance of antioxidant enzymes in the control of CL function during the peri-implantation period. As a luteal phase defect can impact fertility by preventing implantation and early conceptus development in livestock and humans, this review attempts to address the importance of ROSscavenging antioxidant enzymes in the control of mammalian CL function and integrity [119].…”
Section: Relationship Between Progesterone and Oxidative Stress In Rumentioning
confidence: 99%
“…The ROS include superoxide anion (dO 2 d), hydroxyl radical (dOH), nitric oxide (NO), hydrogen peroxide (H 2 O 2 ), and peroxynitrite (ONOOd). ROS are also produced via enzymatic pathways, including the activity of membrane-bound NADH and NADPH oxidases, the activity of xanthine oxidase, the metabolism of arachidonic acid by lipoxygenases and cyclooxygenases (COX), and the mitochondrial cytochrome P450 [119].…”
Section: Relationship Between Progesterone and Oxidative Stress In Rumentioning
confidence: 99%